Are Voters More Likely to Contribute to Other Public Goods? Evidence from a Large‐Scale Randomized Policy Experiment. Issue 1 (22nd August 2013) - Bolsen, Toby; Ferraro, Paul J.; Miranda, Juan Jose
<x xml:space="preserve">Abstract</x> Voting has been described as a contribution to a public good. Are people who vote frequently therefore more likely to contribute to other public goods? Does partisanship affect how likely a person is to engage in these cooperative behaviors? Although surveys suggest that the answer to these questions is "Yes, " few empirical studies examine these questions using observed behaviors. We examine them in the context of a large‐scale, randomized controlled trial to induce voluntary action in a common‐pool resource dilemma. During a drought in the southeastern United States, pro‐social messages that encouraged water conservation were randomly assigned to 35, 000 out of 106, 000 households. Frequent voters in primary and general elections (1990–2008) were substantially more responsive to the messages, but there was no detectable difference in the responses of Republican and Democrat households. Our results suggest that internalized pro‐social preferences promote action for the public good across behavioral contexts.